2000
DOI: 10.1046/j.1469-8137.2000.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tree size and temperature on relative growth rate and its components of Fagus sylvatica seedlings exposed to two partial pressures of atmospheric [CO2]

Abstract: Growth responses of two provenances of European beech (Fagus sylvatica) were studied. The seedlings were grown in closed‐top chambers at four temperature regimes (−2.9 °C below ambient, ambient, +2.3 °C and +4.8 °C above ambient) in combination with two CO2 partial pressures (40 Pa and 74 Pa). Growth was followed by making destructive harvests c. every 25 d from germination in early June to senescence in late September. Allocation patterns were significantly affected by the temperature regimes. However, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
4
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 33 publications
4
34
4
3
Order By: Relevance
“…Pronounced productivity stimulation by higher temperatures was found in various studies on beech (e.g. Piutti and Cescatti 1997;Bruhn et al 2000;Fotelli et al 2005;Saxe and Kerstiens 2005;Overdieck et al 2007). Our data show a productivity increase by about 60% with a 6°C-temperature increase (means of all treatments at 18 and 24°C) which matches well with the results of Overdieck et al (2007) who reported a 50% productivity increase in F. sylvatica saplings with a temperature increase by 4°C.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Pronounced productivity stimulation by higher temperatures was found in various studies on beech (e.g. Piutti and Cescatti 1997;Bruhn et al 2000;Fotelli et al 2005;Saxe and Kerstiens 2005;Overdieck et al 2007). Our data show a productivity increase by about 60% with a 6°C-temperature increase (means of all treatments at 18 and 24°C) which matches well with the results of Overdieck et al (2007) who reported a 50% productivity increase in F. sylvatica saplings with a temperature increase by 4°C.…”
Section: Discussionsupporting
confidence: 91%
“…However, when both parameters were changed synchronously in the 24°C/500 Pa treatment, productivity was about 150% higher than in the 18°C/ 1,000 Pa treatment, which is substantially more than the added temperature and air humidity effects. In European beech, synergy effects were also observed for the combination of temperature and [CO 2 ] (Saxe and Kerstiens 2005;Bruhn et al 2000), temperature and light (Fotelli et al 2005) as well as for the light/soil fertility interaction (Johnson et al 1997). These results underline the importance of multi-factor studies when attempting to predict the response of trees to climatic changes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our findings cannot easily be compared with the results of experiments in controlled-environment chambers which commonly, from the very beginning, show large positive effect of CO 2 on tree growth (e.g. Druart et al, 2006;Bruhn et al, 2000;Tjoelker et al, 1998). In these experiments the potted tree seedlings grew under optimal fertilized condition and were furthermore not affected by competition.…”
Section: Discussioncontrasting
confidence: 57%
“…Druart et al, 2006;Bruhn et al, 2000;Tjoelker et al, 1998), in situ experiments using freeair CO 2 enrichment -FACE (Dawes et al, 2011;Eguchi et al, 2005;Pepin & Körner, 2002;Norby et al, 2001), and in situ studies at naturally CO 2 -enriched sites (Tognetti et al, 2000;Hättenschwiler et al, 1997;Paoletti et al, 2005). Working in mofette areas enables the study of long-term tree-growth response under authentic natural conditions.…”
Section: Introductionmentioning
confidence: 99%